A generic, comprehensive and granular decoder complexity model for the H.264/AVC standard - Semsarzadeh, Mehdi; Hashemi, Mahmoud Reza; Shirmohammadi, Shervin (Journal of visual communication and image representation, 2014)
•To address power consumption concern in video decoders, a model is proposed.•The model is generic: it is designed independent from platform/implementation.•The model is comprehensive: all of the decoding modules are considered in the model.•It is granular: the complexity can be controlled at macroblock level at encoder side.•The model can be used to design a receiver aware encoder (RAE). With recent advances in computing and communication technologies, ubiquitous access to high quality multimedia content such as high definition video using smartphones, netbooks, or tablets is a fact of our daily life. However, power consumption is still a major concern for portable devices. One approach to address this concern is to control and optimize power consumption using a power model for each multimedia application, such as a video decoder. In this paper, a generic, comprehensive and granular decoder complexity model for the baseline profile of H.264/AVC decoder has been proposed. The modeling methodology was designed to ensure a platform and implementation independent complexity model. Simulation results indicate that the proposed model estimates decoder complexity with an average accuracy of 92.15% for a wide range of test sequences using both the JM reference software and the x264 software implementation of H.264/AVC, and 89.61% for a dedicated hardware implementation of the motion compensation module. It should be noted that in addition to power consumption control, the proposed model can be used for designing a receiver-aware H.264/AVC encoder, where the complexity constraints of the receiver side are taken into account during compression. To further evaluate the proposed model, a receiver-aware encoder has been designed and implemented. Our simulation results indicate that using the proposed model the designed receiver aware encoder performs similar to the original encoder, while still being able to satisfy the complexity constraints of various decoders.